Leadership Discourses of Keyae in Islamic Boarding School (Research, Society and Development, 2019)
This study is aimed to discuss the discourse of Keyae in Pesantren (Islamic Boarding School) and its relevance toward Islamic values in Madura, especially. Afterward, this study is conducted by involving the participators in Annuqayah Islamic Boarding School, Guluk-Guluk, Sumenep which is assumed to be representative, and have relevance in protecting Islamic values in Madura. The data which is obtained based on Michel Foucault’s discourse analysis. The reason to choose the theory aims to understand the conditions that supporting the emergence of leadership discourse of Keyae, form and its operational, discontinue and relational, archeology of leadership discourse, and reveal or analyze critics on leadership discourses of Keyae in Madura, specifically in social mechanism. Therefore, based on the analysis, this study shows that leadership of Keyae in Islamic Boarding School in Madura is not merely as an agent of religious movement. However, it is as social, politic, culture, economic, and education transformations.